A Balanced Tri-Band Substrate Integrated Waveguide Bandpass Filter With High Selectivity - Min, Li; Pan, Mingyue; Wang, Dawei; Luo, Zhenhai; Xu, Congcai (Frontiers in Physics, 2022)
This paper proposed a balanced tri-band bandpass filter (BPF) with high selectivity based on substrate integrated waveguide (SIW) technology. The tri-band filtering response and multiple transmission zeros (TZs) are attained by elaborately merging cascaded quadruplet (CQ) topology and split topology. The proposed balanced tri-band bandpass filter is designed, which integrates high selectivity differential-mode (DM) transmission and good common-mode suppression by cleverly placing TE102-mode SIW cavity on the symmetric plane. To verify the proposed concept, a prototype of balanced tri-band BPF operating at 9.33, 9.67, and 10.02 GHz has been implemented. Measured results show eight TZs at out of DM passbands and more than 35 dB CM suppression within the DM passbands, which agree well with the simulated results.